2021
DOI: 10.1088/2057-1976/ac0d91
|View full text |Cite
|
Sign up to set email alerts
|

A deep convolutional neural network model for hand gesture recognition in 2D near-infrared images

Abstract: The hand gesture recognition (HGR) process is one of the most vital components in human-computer interaction systems. Especially, these systems facilitate hearing-impaired people to communicate with society. This study aims to design a deep learning CNN model that can classify hand gestures effectively from the analysis of near-infrared and colored natural images. This paper proposes a new deep learning model based on CNN to recognize hand gestures improving recognition rate, training, and test time. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…ISLR shares a lot of features with action recognition, and consequently there are several works using CNNs for feature extraction and classification [ 32 , 33 , 34 , 35 ]. Recent work has also relied on employing 3D-CNNs [ 36 , 37 ] to capture spatiotemporal information in an ensemble way.…”
Section: Related Workmentioning
confidence: 99%
“…ISLR shares a lot of features with action recognition, and consequently there are several works using CNNs for feature extraction and classification [ 32 , 33 , 34 , 35 ]. Recent work has also relied on employing 3D-CNNs [ 36 , 37 ] to capture spatiotemporal information in an ensemble way.…”
Section: Related Workmentioning
confidence: 99%
“…The data is divided 70% for training, and the remainder of the dataset is equally divided between validation and testing. Also, Can, Kaya, et al [19] suggested a CNN model for colored natural ASL pictures and compared their accuracy with five well-known transfer learning models, including VGG16, VGG19, ResNet50, and DenseNet121, to obtain 99.91% superior to his peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result of other state-of-the-art in literature [17] and [13] on collected but not publicly available datasets are also reported in Table VII. The CNN models proposed in [ [46], [19]] achieved higher accuracy on selected images from the MNIST dataset. However, the proposed SL-CNN model is applied to all images in the recent Kaggle dataset, and the two versions of Massey beat all the previously suggested CNN models.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…The HGR was provided as an outcome from the text format. Can et al (2021) proposed a DL-CNN approach which categorizes hand gestures efficiently in the investigation of near-infrared and color natural images. This paper presents a novel deep learning (DL) technique dependent upon CNN for recognizing hand gestures, enhancing the rate of recognition, testing, and training time.…”
Section: Related Studiesmentioning
confidence: 99%